Oil companies : the new partners of the United Nations : a critique of the type II partnership initiatives in the WSSD (Quito: Oilwatch, 2002)
"Titel op titelpagina: Oil companies : the new partners of the United Nations : a critique of the type II partnership initiativesm in the WSSD"